Обреченный на бой: роман / Р. В. Золотников - Злотников Роман Валерьевич (Армада, 2001)
Экземпляры: ф.2 (2005) / Инвентарный номер: 49524 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: О-55 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-445